2014
DOI: 10.1093/ije/dyu062
|View full text |Cite
|
Sign up to set email alerts
|

Increased carriage of macrolide-resistant fecalE. colifollowing mass distribution of azithromycin for trachoma control

Abstract: MDA resulted in significantly increased prevalence of macrolide resistance in E. coli. Although MDA is effective for trachoma elimination, it has costs; it is essential to monitor antimicrobial resistance following MDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 36 publications
1
61
2
Order By: Relevance
“…This finding might be related to the antibacterial activity, the long post-antibiotic effect plus the anti-inflammatory properties of azithromycin, which might break the vicious circle of diarrhea -gut inflammation -nutrient malabsorption -weakened immune status -diarrhea; directly diminishing the number of diarrhea cases due to the good activity of azithromycin against the most relevant diarrheogenic pathogens, but also reducing gut inflammation, thereby favoring nutrient absorption, and consequently, improving the immune status. In the dark size, this mass use of azithromycin will most likely result in the selection of macrolide-resistant microorganisms, as has been described in Tanzania (Seidman et al, 2014). Long-term follow up of these cohorts is needed in order to determine the longterm effect on the general levels of macrolide resistance.…”
Section: Clinical Usementioning
confidence: 99%
See 1 more Smart Citation
“…This finding might be related to the antibacterial activity, the long post-antibiotic effect plus the anti-inflammatory properties of azithromycin, which might break the vicious circle of diarrhea -gut inflammation -nutrient malabsorption -weakened immune status -diarrhea; directly diminishing the number of diarrhea cases due to the good activity of azithromycin against the most relevant diarrheogenic pathogens, but also reducing gut inflammation, thereby favoring nutrient absorption, and consequently, improving the immune status. In the dark size, this mass use of azithromycin will most likely result in the selection of macrolide-resistant microorganisms, as has been described in Tanzania (Seidman et al, 2014). Long-term follow up of these cohorts is needed in order to determine the longterm effect on the general levels of macrolide resistance.…”
Section: Clinical Usementioning
confidence: 99%
“…In this respect, gut-commensal Enterobacteriaceae may play a role as a reservoir of resistance genes that may be transferred to pathogenic microorganisms (Nguyen et al, 2009;Seidman et al, 2014). Some studies have shown a higher prevalence of TMMR among Gram-negative microorganisms compared to Gram-positive recovered from healthy children (Luna et al, 2002;Ojo et al, 2004), reinforcing the relevance of these antibiotic-resistance reservoirs.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…(Boumghar-Bourtchai et al, 2008). Breakpoints to discriminate between azithromycin resistant and susceptible populations of E. coli were proposed in a study looking at the epidemiology of mass drug treatment of human patients with azithromycin to control trachoma infection (Seidman et al, 2014). The same cutoff value ( 32 mg/L -which is equivalent to the cut-off value of > 16 mg/L used in this report) has been used in epidemiological studies of E. coli in animals (Schmidt et al, 2015).…”
Section: Azithromycin Newly Inserted In the Harmonised Set Of Antimicmentioning
confidence: 99%
“…In Taiwan (19) and other parts of the world, antibiotic prescribing may also be influenced by competition between health care providers and from unsanctioned providers. Mass drug administration of antibiotics for the management of severe acute malnutrition (20) and trachoma control (21) could contribute to resistance at a mass scale if not monitored carefully (22).…”
Section: Conservationmentioning
confidence: 99%